Laboratory time‐resolved X‐ray diffractometry for in situ studies of crystalline materials under uniaxial compression and vibration. Issue 1 (19th January 2022) - Akkuratov, Valentin; Blagov, Alexander; Eliovich, Yan; Targonskii, Anton; Pisarevsky, Yuri; Protsenko, Andrei; Shishkov, Vladimir; Kovalchuk, Mikhail
Abstract : A laboratory diffractometer for time‐resolved high‐resolution X‐ray diffraction studies of reversible and irreversible processes in crystalline materials is presented. Abstract : A novel laboratory diffractometer for time‐resolved high‐resolution X‐ray diffraction studies of reversible and irreversible processes in crystalline materials under uniaxial compression and vibration is described. Temporal resolution up to milliseconds for double‐crystal and up to tens of seconds for triple‐crystal diffraction experiments was achieved with a single adaptive bending X‐ray optics element. Design solutions and techniques for applying and controlling uniaxial compression and vibration for in situ time‐resolved studies are described. Results are presented for various static and dynamic load experiments, controlled by a system based on the TANGO Controls framework. Rocking curves of paratellurite (TeO2 ) under quasi‐static compression and lithium fluoride (LiF) under ultrasonic vibration were measured with temporal resolution. Reciprocal‐space maps of LiF under static compression and quartz (SiO2 ) under ultrasonic vibration were collected.